Coupling ratio tuning of direct UV-written X-couplers for cascaded power splitters in WDM networks - Adikan, Faisal Rafiq Mahamd; Gates, J.C.; Gawith, C.B.E.; Smith, P.G.R. (2006)
Presented is a study of low polarisation sensitivity 2 degrees X-couplers with 20 coupling ratio tuning via refractive index asymmetry, attaining 50:50 power splitting at 1550 nm. The device has less than 5 coupling ratio variation over 30 nm in the C-band and < 0.7 dB polarisation-dependent loss.